2010
DOI: 10.1021/jf1031668
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Ameliorates Experimental Lung Fibrosis Both in Vivo and in Vitro: Implications for Therapy of Lung Fibrosis

Abstract: Lonicera japonica (Caprifoliaceae) has been known as an anti-inflammatory herb in traditional Chinese medicine for thousands of years and is used constantly for upper respiratory tract infections. Luteolin, an active flavonoid compound isolated from Lonicera japonica, has a spectrum of biological activities, especially with antioxidative and anti-inflammatory properties. However, whether luteolin has a direct inhibitory effect on lung fibrosis has not been established. In this study, we examined the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 34 publications
4
65
0
1
Order By: Relevance
“…For example, luteolin reduces Muc5ac expression stimulated by epidermal growth factor or phorbol 12-myristate 13-acetate in NCI-H292 cells37. Luteolin inhibits bleomycin-induced lung fibrosis46 and alleviates OVA-induced bronchoconstriction and airway hyperreactivity39. Consistent with previous studies, we also found that luteolin suppressed OVA-induced IL upregulation and AHR, suggesting that luteolin may be used as an anti-asthmatic agent.…”
Section: Discussionsupporting
confidence: 89%
“…For example, luteolin reduces Muc5ac expression stimulated by epidermal growth factor or phorbol 12-myristate 13-acetate in NCI-H292 cells37. Luteolin inhibits bleomycin-induced lung fibrosis46 and alleviates OVA-induced bronchoconstriction and airway hyperreactivity39. Consistent with previous studies, we also found that luteolin suppressed OVA-induced IL upregulation and AHR, suggesting that luteolin may be used as an anti-asthmatic agent.…”
Section: Discussionsupporting
confidence: 89%
“…The oral administration of luteolin (10 mg/kg) has been shown to effectively suppress neutrophil infiltration, as well as the increase in TNFα and IL-6 levels in bronchoalveolar lavage fluid from bleomycin-instilled C57BL/6J mice (36). Luteolin injected intraperitoneally at different doses of 10 or 25 mg/kg has also beehn shown to significantly increase SOD1 activity and decrease MDA levels in mice with permanent middle cerebral artery occlusion, which results in alleviated neurological deficits, infarct volume and brain water content (37).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of lung tissue inflammation was evaluated quantitatively by H&E staining method. A score ranging from 0 to 4 was assigned according to severity, and the scores were averaged per group [21]. The Masson's trichrome staining method was used to investigate fibrotic degree.…”
Section: Histopathological Assessmentmentioning
confidence: 99%